OPTIMASI PERMUKAAN RESPON KUADRATIK MENGGUNAKAN ANALISIS RIDGE - , YUFAN PUTRI ASTRINI ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Response surfaces method is a method that aims to determine the optimal operating conditions in an experiment. The response characteristics of operating conditions can be a maximum, minimum, or saddle point. In some situations where a stationary point has no value, for example, a stationary point is at the saddle point and stationary point which causes minimum or maximum response point outside the original region, needs to be done a specific analysis to handle that. This analysis called ridge analysis. Ridge analysis is a useful procedure to optimize response prediction in hyperspherical centralized quadratic model. This procedure calculates the estimated ridge on the optimum response for increasing radii from the center of the actual experiments. The case study used in this thesis is the optimization of the power torque TL lights against low air, low air cooling, and natural gas pressure. Experimental design using central composite design (CCD) with the number of experiments at 23 runs. The analysis showed that the optimal condition is obtained when the pressure of low air 3,80125 Kpa, low air cooling 7,3515 Kpa, and natural gas 4,97 Kpa, that is when the strength of the torque reaches 3,11125 Newton meter.